Anti-cancer drugs associated with sudden death and ventricular arrhythmias: a cardio-oncology pharmacovigilance analysis. (25th November 2020) - Mirabel, M; Karapetiantz, P; Marijon, E; Le Beller, C; Reda Al-Sayed, Z; Boutouyrie, P; Jouven, X; Lillo-Lelouet, A; Hulot, J.S
Abstract: Background: Experimental data have shown that some anticancer drugs can affect cardiac repolarization and induce life-threatening cardiac arrhythmias. Objective: To identify anti-cancer drugs associated with the occurrence of sudden death (SD) and ventricular arrhythmias using the World Health Organization individual case safety report (ICSR) database, Vigibase. Methods: The system organ class MEDRA was used to identify cases as ICSR with the terms sudden death, sudden cardiac death, cardiac arrest, ventricular fibrillation, ventricular tachycardia, ventricular arrhythmia and torsades de pointes (named as SD events) from Nov 1967 to Nov 2019. We used the ATC code L01 which regroups 219 antineoplastic agents. A disproportionality analysis was performed to estimate of relative Odds Ratio (ROR). Signals were considered significant when the lower boundary of the 99.97% confidence interval (ROR0.25) was ≥1. Results: Among the 2, 170, 203 adverse events associated with anticancer drugs, 11, 979 (0.55%) concerned SD events. A total of 49 molecules were significantly associated with SD events, among which 4 were withdrawn from market. These molecules were mainly anti-metabolites (20.0%), chemicals such as arsenic (17.8%, ), anthracyclins (8.9%) and alkaloids (8.9%). When agents were grouped according to their mode of actions, the highest risks were observed for platinum-based drugs (n=1628 cases, ROR0.25=1.2) and anthracyclins (n=1323 cases, ROR0.25=1.3). While the risk for SD or severe arrhythmias was reported in the drug label for 29 agents (64.4%), we found that this risk was not identified or mentioned for 16 agents (35.5%). Conclusions: We identified 49 anticancer drugs that are significantly associated with SD events overreporting. Appropriate monitoring and preventive measures should be considered for patients receiving these drugs. Funding Acknowledgement: Type of funding source: None